2021
DOI: 10.1371/journal.pone.0245486
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical presentation of glaucoma in a referral facility in Ghana: Any lessons for public health intervention?

Abstract: The purpose of this study was to evaluate the epidemiological and clinical profile of patients living with glaucoma and receiving care in a tertiary eye center in Ghana. This was a hospital-based retrospective study of clinical records of glaucoma patients from January 2010 to December 2019. The study involved collating demographic information of patients, clinical presentation, and the management of glaucoma. A total of nineteen thousand (19,000) charts were retrieved from the eye center’s archives. Out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The present study found no significant difference in glaucoma prevalence between male and females, which was similar to previous studies from Ghana [ 44 , 45 ]. In contrast, studies from Nigeria [ 5 , 40 , 41 ], Ghana [ 46 ] and South Korea [ 44 ] reported a higher prevalence in men than women. Moreover, gender predilection of glaucoma has not been established suggesting the need for more studies to determine the association of glaucoma with gender.…”
Section: Discussionmentioning
confidence: 94%
“…The present study found no significant difference in glaucoma prevalence between male and females, which was similar to previous studies from Ghana [ 44 , 45 ]. In contrast, studies from Nigeria [ 5 , 40 , 41 ], Ghana [ 46 ] and South Korea [ 44 ] reported a higher prevalence in men than women. Moreover, gender predilection of glaucoma has not been established suggesting the need for more studies to determine the association of glaucoma with gender.…”
Section: Discussionmentioning
confidence: 94%
“…The eye care workforce at this specialist eye centre consisted of ophthalmologists, optometrists, ophthalmic nurses and opticians. The daily ophthalmic patient attendance to the facility averages one hundred, of which close to 30% are glaucoma patients [7].…”
Section: Study Settingmentioning
confidence: 99%
“…The sample for this study was 400 patients with POAG who were systematically sampled when they reported for routine reviews at this specialist eye facility. The sample size was determined using the formula N = Z 2 (1-p) (p)/b2, where N = minimum sample size, z = the standard normal deviation, set at 1.96 which corresponds to the 95% con dence interval, p = estimated prevalence of 30% [7], b = degree of accuracy desired, usually set at 5%. Per this equation, the sample size was determined to be 323 which was adjusted to 400 participants to account for attrition rate and ine ciencies associated with the small sample size.…”
Section: Study Design and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Glaucoma is an eye disease characterized by intermittent or continuous increase in intraocular pressure [1] . Currently, there are nearly 600 million patients with glaucoma worldwide, of whom 8.4 million suffer from blindness [2] . The pathogenesis of glaucoma, a kind of degenerative and blinding optic neuropathy caused by multiple factors, is complicated [3] and its clinical manifestations are primarily optic atrophy, visual field damage and Retinal Ganglion Cell (RGC) apoptosis.…”
mentioning
confidence: 99%